Effect of Breed on the Composition of Cow Milk under Traditional Management Practices in Ado-Ekiti, Nigeria - K Adesina (Journal of Applied Sciences and Environmental Management)
Studies on the effect of breed on the composition of cow milk kept under traditional management practices in Ado-Ekiti were carried out. Twelve lactating cows comprising four each of white Fulani (WF), Red Bororo (RB) and Muturu (MT) breeds were hand-milked 7 days post-partum before morning grazing. Representative samples of milk obtained from four cows of each breed were bulked separately and analysed for proximate, mineral and amino acids composition. The ash, protein and lactose contents of the milk did not differ significantly among the three cow breeds. However, breed of cow had significant effect on the water and fat compositions with milk fat varying extensively. The essential minerals like Ca, K, P, Na, Fe, Mg, Mn, Zn and Cu were detected in measurable concentrations ranging from 0.05 to 1.53mg/1, 0.06 to 151.5mg/1 and 0.09 to 1445mg/1 for WF, RB and MT breeds respectively. The result showed that breed of cow has no significant effect on the mineral and amino acids composition of the milk. Generally, the compositional variation of milk under study typified those of dairy herds earlier reported.